2022
DOI: 10.1158/2767-9764.crc-21-0176
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of the Nuclear Transport Protein XPO1 Enhances the Anticancer Efficacy of KRAS G12C Inhibitors in Preclinical Models of KRAS G12C–Mutant Cancers

Abstract: The identification of molecules that can bind covalently to KRAS G12C and lock it in an inactive GDP-bound conformation has opened the door to targeting KRAS G12C selectively. These agents have shown promise in preclinical tumor models and clinical trials. FDA has recently granted approval to sotorasib for KRAS G12C mutated non-small cell lung cancer (NSCLC). However, patients receiving these agents as monotherapy generally develop drug resistance over time. This necessitates the development of multi-targeted … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…There is a growing understanding of the importance of identifying synthetic lethality associated with KRAS and developing small molecule inhibitors that target these synthetic lethal targets. Previously, we had experimentally validated synthetic lethal interactions of KRASG12C inhibitors with nuclear export protein XPO1 inhibitor in silico, in vitro and in vivo [26]. In this study, the identification of the existence of synthetic lethality between PAK4 and KRAS using the Slorth database rationalizes the significance of co-targeting PAK4 and KRAS.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…There is a growing understanding of the importance of identifying synthetic lethality associated with KRAS and developing small molecule inhibitors that target these synthetic lethal targets. Previously, we had experimentally validated synthetic lethal interactions of KRASG12C inhibitors with nuclear export protein XPO1 inhibitor in silico, in vitro and in vivo [26]. In this study, the identification of the existence of synthetic lethality between PAK4 and KRAS using the Slorth database rationalizes the significance of co-targeting PAK4 and KRAS.…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we had experimentally validated synthetic lethal interactions of KRASG12C inhibitors with nuclear export protein XPO1 inhibitor in silico, in vitro and in vivo [26]. In this study, the identification of the existence of synthetic lethality between PAK4 and KRAS using the Slorth database rationalizes the significance of co-targeting PAK4 and KRAS.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, the combined targeting of KRAS G12C with cell cycle checkpoints or immune checkpoints is promising [ 50 , 72 , 117 ]; the triple combined inhibition of KRAS G12C /SHP2/PD-L1 leads to severe tumor regression in PDAC mouse models [ 108 ]. Recent studies have shown that the nuclear export protein exportin 1 (XPO1) relieves tumor cells from resistance to KRAS G12C inhibitors [ 118 ]. This effect has been demonstrated in a mouse xenograft model.…”
Section: Strategies To Circumvent Drug Resistancementioning
confidence: 99%
“…5,6 Selinexor is a first-in-class, selective inhibitor of nuclear export and binds covalently to Exportin 1. 3,7,8 Studies have demonstrated that selective inhibitors of nuclear export can block the growth of both NSCLC cell lines and xenografts alone, 9 and with targeted agents, such as the KRAS G12C inhibitors, 10 Bcl-xL inhibitor A-1331852, 11 poly(ADP-ribose) polymerase inhibitor BMN673 (12), and chemotherapeutic agents such as cisplatin. 13 It has been shown to reduce the protein levels of driver oncogenes, such as MYC and EGFR, in multiple cancer types.…”
Section: Introductionmentioning
confidence: 99%